Analisis Faktor-Faktor Yang Mempengaruhi Stres Pada Mahasiswa UNU Kalbar Angkatan 2018 Dalam Menyusun Skripsi - Misningsih Misningsih; Yuni Firayanti; Mazayatul Mufrihah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to find out the factors that influencing stress on UNU West Kalimantan students Batch 2018 in compiling thesis. the method in this study uses a Quantitative Descriptive technique data collection using a questionnaire. The data analysis technique used is spss 25 program. This research was conducted at Nahdlatul Ulama University, West Kalimantan, with the number of respondents as many as 44 people. The research results show that there are 2 influencing factors in student stress, namely internal factors which include (Frustration, conflict, pressure,Self- inposed (self-imposed)) and external factors namely (Family, campus) research shows that there is an intermediate effect internal factors and external factors on student stress in preparing thesis.